Nigella sativa and health outcomes: An overview of systematic reviews and meta-analyses - Li, Zhongyu; Wang, Yang; Xu, Qing; Ma, Jinxin; Li, Xuan; Yan, Jiaxing; Tian, Yibing; Wen, Yandong; Chen, Ting (Frontiers in Nutrition, 2023)
Background Nigella sativa (N. sativa) consumption has been associated with various health outcomes; however, the results are not completely consistent. Objectives This overview of systematic reviews and meta-analyses aimed to evaluate the reporting and methodological quality, and to grade the available evidence of associations between N. sativa and health outcomes. Methods PubMed, Cochrane Library, Embase, and Scopus databases were searched from their inception to September 30, 2022. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2009 statement, Assessment of Multiple Systematic Reviews (AMSTAR) 2 checklist, and Grades of Recommendations, Assessment, Development and Evaluations (GRADE) systems were used to assess the reporting, methodological, and evidence quality for each meta-analysis, respectively. The results were synthesized in a narrative form. Results This overview included 20 eligible meta-analyses published in peer-reviewed journals between 2013 and 2021. The overall methodological quality was relatively poor, with only one moderate quality, four low quality, and 15 critically low quality studies. For reporting quality, items two, five, eight, nine, 15, and 24 need to improve. Among the 110 outcome indicators of the quality of evidence, five were graded as moderate, 17 as low, and 88 as very low. Risk of bias, inconsistency, and imprecision were the main downgrading factors. Conclusion This overview suggests that N. sativa is beneficial for various clinical outcomes. However, there are certain limitations to reporting and methodological quality. The clinical efficacy of N. sativa requires confirmation in high-quality, large-sample, randomized controlled trials.